Fragmentation in the european retail deposit market and implications for loan availability in european member states - Mark Wahrenburg; Bijan Kaffenberger (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
European households face tremendous obstacles when intending to open a savings account outside their home country. The shortage of deposits has become a major reason for banks declining loan supply and ultimately is responsible for a substantial part of the investment weakness and GDP decline in affected European countries. Policy makers have made important efforts to promote European deposit market integration and to stimulate cross border flows of savings within the European Union. But these efforts will only yield the intended benefits if a number of additional non-tariff trade barriers are removed. Currently, these barriers prevent households in surplus countries to transfer their savings to banks in deficit countries where their deposits are most urgently needed.
urn:nbn:de:hebis:30:3-391162
Keywords: 330; European market fragmentation; deposits; household finance